2000
DOI: 10.2138/am-2000-5-615
|View full text |Cite
|
Sign up to set email alerts
|

Compression mechanism of brucite: An investigation by structural refinement under pressure

Abstract: Synchrotron X-ray powder diffraction study of brucite, Mg(OH) 2 , was carried out in a diamond anvil cell with an imaging plate detector from 0.6 to 18.0 GPa at room temperature using the angular-dispersive technique on beamline BL-18C at the Photon Factory, KEK, Japan. Using Rietveld analysis, unit-cell parameters as well as atomic positions of the O atoms in brucite have been successfully refined, taking into account the effects of preferred orientation. Variation of the c/a ratio with pressure indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 17 publications
8
51
1
Order By: Relevance
“…13) (distinct from the amorphization observed in powder samples 11 ). Remarkable similarities were reported between the Raman spectra of the high-pressure phase of single-crystal Ca(OH) 2 and Sr(OH) 2 , and it is notable that the c/a ratio and many of bond lengths in Cd(OH) 2 are similar to those in Ca(OH) 2 (Table I). The spectra of the high-pressure phases of Cd(OH) 2 and Ca(OH) 2 are also closely similar: A sharper new peak appears on the high-frequency side of the A 1g (OH) mode during the phase transition in Ca(OH) 2 which is very similar to the new mode we observed near A 1g (OH) in Cd(OH) 2 (ν 7 in Fig.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…13) (distinct from the amorphization observed in powder samples 11 ). Remarkable similarities were reported between the Raman spectra of the high-pressure phase of single-crystal Ca(OH) 2 and Sr(OH) 2 , and it is notable that the c/a ratio and many of bond lengths in Cd(OH) 2 are similar to those in Ca(OH) 2 (Table I). The spectra of the high-pressure phases of Cd(OH) 2 and Ca(OH) 2 are also closely similar: A sharper new peak appears on the high-frequency side of the A 1g (OH) mode during the phase transition in Ca(OH) 2 which is very similar to the new mode we observed near A 1g (OH) in Cd(OH) 2 (ν 7 in Fig.…”
Section: Discussionsupporting
confidence: 58%
“…This is mainly due to the fact that the O-H units are distant from each other along the a-axis, in comparison with the other hydroxides (see O-O in Table I). Among the transition-metal hydroxides (M = Ni, Co, Fe, Mn, and Cd), the magnitudes of the bond lengths and angle are the largest for Cd(OH) 2 (Table I). Therefore, it is of particular interest to compare the behavior of Cd(OH) 2 to Ca(OH) 2 and other transition-mental hydroxides under pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Very similar behavior has been observed in the layered materials Mg(OH) 2 (brucite), [27] Mn ( It is tempting to use bond valence sum techniques [29] to estimate the change in the effective Ço oxidation state, based on the change in the Co-O bond length. Such calculations suggest a change in the Co oxidation state as large as 0.1 electrons over the 0.6 GPa pressure range of this study.…”
Section: Resultsmentioning
confidence: 52%
“…However, all of these measurements were conducted without a pressure transmitting medium [Meade and Jeanloz, 1990;Duffy et al, 1995], or with a rigid silicon oil medium [Nagai et al, 2000]. Ekbundit et al [1996] confirmed the amorphization in powder samples but reported a transition to a crystalline phase occurring at 6 GPa and room temperature in single crystal Ca(OH) 2 .…”
Section: Introductionmentioning
confidence: 87%